2012
DOI: 10.1073/pnas.1116421109
|View full text |Cite
|
Sign up to set email alerts
|

Divergent role of the Hox gene Antennapedia in spiders is responsible for the convergent evolution of abdominal limb repression

Abstract: Evolution often results in morphologically similar solutions in different organisms, a phenomenon known as convergence. However, there is little knowledge of the processes that lead to convergence at the genetic level. The genes of the Hox cluster control morphology in animals. They may also be central to the convergence of morphological traits, but whether morphological similarities also require similar changes in Hox gene function is disputed. In arthropods, body subdivision into a region with locomotory app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 48 publications
3
86
0
4
Order By: Relevance
“…In insects, the Antp gene is highly conserved in its morphological homeotic function, specifying segment identity. In a non-insect arthropod, the spider A. tepidariorum, the Antp gene represses the development of legs in the first segment of the abdomen (Khadjeh et al, 2012). Our data showed that homozygous mutation in BmAntp produced the fused thorax and antennae-like appendages between the head and the thorax (Figure 1).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In insects, the Antp gene is highly conserved in its morphological homeotic function, specifying segment identity. In a non-insect arthropod, the spider A. tepidariorum, the Antp gene represses the development of legs in the first segment of the abdomen (Khadjeh et al, 2012). Our data showed that homozygous mutation in BmAntp produced the fused thorax and antennae-like appendages between the head and the thorax (Figure 1).…”
Section: Discussionmentioning
confidence: 62%
“…Ectopic expression of the Antp gene leads to distinct phenotypes, such as the transformation of antennae into second legs and eye reduction (Schneuwly et al, 1987;Plaza et al, 2008;Prince et al, 2008). Moreover, in the spider Achaearanea tepidariorum, a non-insect arthropod, the Antp gene represses the growth of legs in the first segment of the abdomen (Khadjeh et al, 2012). There are reports of extensive studies, but further exploration of the particular role of the Antp gene underlying the development of the thorax and thoracic appendages is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Concordantly, functional data have demonstrated that the spider Antp orthologue represses limb development in the opisthosoma of Parasteatoda tepidariorum [30]. By contrast, expression dynamics of hth are more comparable to insect counterparts.…”
Section: Introductionmentioning
confidence: 51%
“…Indeed, Hth and Exd are bona fide Hox cofactors in D. melanogaster [22,44 -46]. However, functional data for chelicerate Hox genes are limited to analysis of Antp, and thus the interaction of hth and anterior Hox genes is unknown for chelicerates [30]. In addition, Antp in the spider P. tepidariorum appears to have a function that is convergent upon the role of Ultrabithorax in insects (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Because targeted misexpression is not yet available in P. tepidariorum, we achieved activation of lab-1 in the L1 segment by interfering with the function of the Hox gene Dfd. Dfd is expressed in all four walking leg segments and thus posteriorly adjacent to the pedipalpal segment [21]. RNAi with Dfd leads to the ectopic expression of lab-1 (figure 3d,e), but not of lab-2 (figure 3f ), in the L1 segment.…”
Section: Resultsmentioning
confidence: 99%